FAKTOR FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL (Studi Empiris pada Perusahaan Property dan Real Estate yang terdaftar di Bursa Efek Indonesia Tahun 2010-2014) - Jusrizal Jusrizal; Aloysius H. (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2017)
The aims of this research is to understand the factors affecting the capitalstructure for Property and Real Estate companies enlisted in Indonesian Stock Exchange period 2010-2014. Samples are 31 Property and Real Estate company in Indonesian Stock Exchange, where the method used is purposive sampling is a sampling method by specifying certain criteria for 5 years so the amount of data as much as 155. The method of data analysis using multiple linear regression and using software Eviews 7. This research have five variables : four independent variables: profitability, asset structure, company size, growth asset and one dependent variable: capital structure. The result of this research shows that Profitability, Asset Structure, Company Size, and Growth Asset simultaneous significant effect on Capital Structure. The result also showed that Asset Structure partially significant negative effect on Capital Structure, while the Profitability, Company Size and Growth Asset partially no significant effect on Capital Structure.